Health status and self-perception of health among homeless people in Spain: a mixed-methods study - Bedmar, Miguel A.; Capitán-Moyano, Laura; Bennasar-Veny, Miquel; Moreno-Mulet, Cristina; Carrero-Planells, Alba; Yáñez, Aina M. (Frontiers in Public Health, 2024)
Introduction Homelessness is a phenomenon of social exclusion and poverty that has increased alarmingly during recent years. Homeless people (HP) experience violations of several basic human rights or needs that impact their well-being. Therefore, the aim of this research was to assess the health status and self-perceived health of HP and examining the impact of homelessness on their health. Methods We used an explanatory sequential mixed-methods approach that integrated a quantitative cross-sectional study within critical social and ethno-sociological qualitative frameworks. Data were collected in Palma, Spain, from December 1, 2020, to January 1, 2023. A total of 198 HP were recruited from the streets and public areas. Basic human needs (Virginia Henderson model), medical diagnoses, substance abuse (DAST-10), diet quality (IASE), depression (PHQ-9), and social support (SSQ-6) were assessed. Then, 17 semi-structured interviews were conducted and were analyzed using thematic content and discourse analysis. Quantitative and qualitative data were integrated and jointly analyzed. Results The 79.3% of the participants were men, mean age of 47.8 ± 12.2 years. The 76.4% were Spanish. The participants reported severe difficulties in accessing the labor market, and that this greatly affected their self-esteem and mental health. The 48.9% of the participants suffered from one or more chronic diseases, and 50.3% were diagnosed with a mental health disorder. The participants generally did not consider health problems as a central concern. The health needs that most affected the participants were related to food, safety, and social support. HP frequently felt unsafe, fearfully, and anxious. Conclusion Homelessness, unemployment, and social exclusion have significant negative impacts on the health and wellbeing of HP. Precarious work conditions and deficiencies in the welfare system contribute significantly to homelessness. These results highlight the need for systemic solutions that extend beyond short-term housing initiatives.